2018
DOI: 10.7759/cureus.3111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of the IllumiScan Fluorescence Visualization Device in Detecting Oral Mucosal Lesions

Abstract: Objective: Fluorescence visualization devices are screening devices that can be used to examine lesions of the oral mucosa non-invasively. We observed oral squamous cell carcinoma (OSCC) and leukoplakia using the IllumiScan (Shofu, Kyoto, Japan) fluorescence visualization device and examined its usefulness and characteristics.Methods: We investigated 31 OSCC and nine leukoplakia in patients who were examined using the IllumiScan and treated in our department from January 2017 to February 2018. Images taken wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…These changes led to additional scattering and decreased FI compared to the LGD stage, which manifested as an area of low intensity in the HGD/CIS stage. This decrease in FI with tumor progression has been reported in human patients as the same change in FI through the early stages to late stage cancer 26 . The epithelium was showed extensive scattering in the Cancer stage, appearing as dark spots like HGD/CIS.…”
Section: Discussionsupporting
confidence: 80%
“…These changes led to additional scattering and decreased FI compared to the LGD stage, which manifested as an area of low intensity in the HGD/CIS stage. This decrease in FI with tumor progression has been reported in human patients as the same change in FI through the early stages to late stage cancer 26 . The epithelium was showed extensive scattering in the Cancer stage, appearing as dark spots like HGD/CIS.…”
Section: Discussionsupporting
confidence: 80%
“…One of the reasons for this is as follows. The CV of FI in images may indicate intra-tumour heterogeneity [ 19 , 36 ]. Kosugi et al [ 37 ] quantitatively evaluated the changes in FI during progression in the transformation from normal epithelium to SCC in rats and reported that the FI variability increased with progression.…”
Section: Discussionmentioning
confidence: 99%
“…Although many devices have been developed and commercialised to evaluate tissue autofluorescence, the VELscope ® (LED Dental Inc., Vancouver, BC, Canada) was the first commercial auto-focus imaging device approved for oral use in 2008 [ 4 , 17 ]. The IllumiScan ® (Shoufu, Kyoto, Japan) ( Figure S1 ) is an FV device that emits a 425 nm blue light and receives images of the fluorescence generated by the mucosa [ 18 , 19 ]. The light received includes autofluorescence from the mucosa, reflected light, and red fluorescence from bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of objective evaluation in this study, we set various factors, such as MeanV and MediV. MeanV was reported to contribute to the detection of oral cancer [ 15 , 16 , 48 ]. On the other hand, Kozakai also reported that it is difficult to distinguish oral cancer from OLP [ 49 ].…”
Section: Discussionmentioning
confidence: 99%